1993
DOI: 10.1002/ajhb.1310050603
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pulsatile patterns of growth hormone release in humans: A brief review

Abstract: Growth hormone (GH) is an important metabolic hormone, which stimulates net protein anabolism, lipolysis, and linear bone growth. Pulses of GH secretion arise from interactions of hypothalamic GH-releasing hormone and somatostatin at the somatotroph cell in the anterior pituitary gland. The frequency and amplitude of GH pulses are regulated by multiple factors including age, geneder, pubertal status, menstrual cycle phase, body composition, sleep, nutrition, and exercise. In diseases such as obesity, type I di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Exogenous factors, such as photic conditions, also affect the secretion of GH. Spontaneous GH secretion shows a distinct increase during the night in humans (Finkelstein et al 1972;Hartman et al 1993), monkeys (Kaler et al 1986) and rats (Davies et al 2004). In ruminants, it was reported that GH was secreted with an ultradian rhythm with higher peaks in the daytime than nighttime in male calves (Hänninen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous factors, such as photic conditions, also affect the secretion of GH. Spontaneous GH secretion shows a distinct increase during the night in humans (Finkelstein et al 1972;Hartman et al 1993), monkeys (Kaler et al 1986) and rats (Davies et al 2004). In ruminants, it was reported that GH was secreted with an ultradian rhythm with higher peaks in the daytime than nighttime in male calves (Hänninen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous GH secretion shows a distinct increase during the night in humans (Finkelstein et al . 1972; Hartman et al . 1993), monkeys (Kaler et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although prohibited in sports there is not yet an approved method to detect hGH abuse. The simple quantification of hGH in serum is not capable to detect growth hormone abuse as hGH is secreted in a pulsatile manner [1].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the rat, sexually dimorphic GH profiles have been reported in turkeys, sheep, horses, mice, chickens (cf. Shapiro et al, 1995), and humans (Hartman et al, 1993;Van den Berg et al, 1996;Engstrom et al, 1998). In humans, numerous reports, generally using GH-deficient individuals, have shown that GH replacement can restore drug-metabolizing enzymes to normal levels (Redmond et al, 1980;Cheung et al, 1996).…”
mentioning
confidence: 99%